Time‐calibrated genomic evolution of a monomorphic bacterium during its establishment as an endemic crop pathogen. Issue 8 (31st December 2020) - Richard, Damien; Pruvost, Olivier; Balloux, François; Boyer, Claudine; Rieux, Adrien; Lefeuvre, Pierre
Abstract: Horizontal gene transfer is of major evolutionary importance as it allows for the redistribution of phenotypically important genes among lineages. Such genes with essential functions include those involved in resistance to antimicrobial compounds and virulence factors in pathogenic bacteria. Understanding gene turnover at microevolutionary scales is critical to assess the pace of this evolutionary process. Here, we characterized and quantified gene turnover for the epidemic lineage of a bacterial plant pathogen of major agricultural importance worldwide. Relying on a dense geographic sampling spanning 39 years of evolution, we estimated both the dynamics of single nucleotide polymorphism accumulation and gene content turnover. We identified extensive gene content variation among lineages even at the smallest phylogenetic and geographic scales. Gene turnover rate exceeded nucleotide substitution rate by three orders of magnitude. Accessory genes were found preferentially located on plasmids, but we identified a highly plastic chromosomal region hosting ecologically important genes such as transcription activator‐like effectors. Whereas most changes in the gene content are probably transient, the rapid spread of a mobile element conferring resistance to copper compounds widely used for the management of plant bacterial pathogens illustrates how some accessory genes can become ubiquitous within a population over short timeframes.